Analisis Empiris Atas ORDPATH Encoding Untuk Kinerja Insert Node Pada Ordered XML Tree - Zamanhuri, Irvanizam (Universitas Atma Jaya Yogyakarta, 2015)
Abstract. The eXtensible Markup Language (XML) has quickly become the de facto standard for data exchange via web. An XML document can be viewed as an ordered tree that has at least one node. Each node must be labeled by using a scheme approach to describe the XML data structure. There are two famous existing encodings, namely Dewey and Inteval Encodings. In this paper, ORDPATH encoding based on Dewey together with the two other encodings are empirically demontrated on dblp, nasa, and treebank datasets. The results show that while a new node was inserted into the tree, Dewey and Interval have to relabel the inserted nodeÃ¢â‚¬â„¢s siblings and modify the interval number of the sibling nodes, respectively. Whereas, the ORDPATH eliminates this problem by adding an even number used as a caret for the new insertion node.Keywords: Ordered Tree, XML, ORDPATH.Ã‚Â Abstrak. EXtensible Markup Language (XML) terus menjadi standard untuk penukaran data melalui web. Sebuah dokumen XML dapat ditinjau menjadi tree terurut yang berisikan sedikitnya satu node. Setiap node harus dilabelkan menggunakan sebuah algoritma pelabelan untuk mendeskripsikan struktur data XML tersebut. Ada dua algoritma encoding yang terkenal selama ini, Dewey dan Interval encoding. Pada tulisan ini, metode ORDPATH yang berbasiskan Dewey bersama-sama dengan Dewey dan Interval didemontrasikan secara empiris dengan menggunakan dataset dblp, nasa, dan treebank. Hasil menunjukkan bahwa ketika node baru dimasukkan ke dalam tree, Dewey dan Interval harus melakukan pelabelan kembali dan memodifikasi interval sibling node. Akan tetapi, ORDPATH dapat mengatasi masalah ini dengan memberikan angka genap yang digunakan sebagai penanda untuk node baru.Kata Kunci: Ordered Tree, XML, ORDPATH.